Diabetes Epidemics in Korea: Reappraise Nationwide Survey of Diabetes "Diabetes in Korea 2007" - Park, Ie Byung (Korean Diabetes Association, 2013)
There are many studies on the prevalence, clinical characteristics, and economic burden of diabetes across the past four decades in Korea. Nonetheless, there is a dearth of nationwide study regarding diabetes encompassing all age group. Eight years ago, the Committee on the Epidemiology of Diabetes Mellitus of Korean Diabetes Association collaborated with Health Insurance Review & Assessment Service to evaluate the status of diabetes care and characteristics in diabetic patients in Korea. In 2007, the collaborative task force team published a comprehensive survey titled "Diabetes in Korea 2007." In this review, we reappraise the diabetic epidemics from the joint report and suggest further studies that are needed to be investigated in the future.